Ethnic Interaction and Multicultural Memory in Pematangsiantar: An Urban Social History - Ahmad Muhajir; Adam Zaki Gultom (Medan Resource Center, 2026)
This article examines ethnic interaction and multicultural memory in Pematangsiantar through urban social history. It addresses the tendency to treat the city’s multiculturalism mainly as a contemporary discourse of harmony, while neglecting the historical processes that produced it. Using historical methods, the study analyzes colonial and administrative records, demographic data, local historical studies, urban heritage literature, and previous research on multiculturalism and ethnic adaptation. The article argues that Pematangsiantar’s plural character emerged from the interaction of local Simalungun society, migrant communities, colonial urban restructuring, market networks, religious institutions, settlements, and educational spaces. These interactions generated both cooperation and inequality, making multiculturalism a negotiated historical process rather than a static condition. The study also shows that multicultural memory is embedded in urban spaces and public narratives but may weaken when historical sites and local histories are neglected.